Alginate-like exopolysaccharides extracted from different waste sludges exhibit varying physicochemical and material properties - Rehman, Zahid Ur; Ghaani, Masoud; Mohamed, Ahmed Y. A.; Gallagher, John; Saikaly, Pascal E.; Ali, Muhammad (Frontiers in Microbiology, 2024)
This study examined the influence of different wastewater treatment processes on the physicochemical properties of Alginate-Like Exopolymers (ALE) extracted from waste sludge. Sludge samples were collected from wastewater treatment plants (WWTPs) processing both combined industrial and domestic wastewater, as well as domestic wastewater alone. Among the processes studied, aerobic granular sludge (AGS) produced the highest ALE yield (352 ± 50 mg/g-VSsludge), significantly exceeding that from membrane bioreactor (170 ± 41 mg/g-VSsludge) and conventional activated sludge (<130 mg/g-VSsludge). AGS-derived ALE also had the highest uronic acid content (224 ± 14.5 mg/g-VSsludge), with mannuronic acids playing a critical role in enhancing hydrogel cohesion and stability. The results showed that the distinct microbial consortium in the AGS system, including the presence of Pseudomonas alcaligenes, was strongly associated with increased ALE production. This establishes a novel link between microbial community composition and ALE yield. These insights are crucial for optimizing resource recovery in AGS systems and underscore the potential of ALE for various industrial applications.